(Table 1) Percentage of non-opaque heavy minerals, heavy residue, magnetite, and opaque heavy minerals, DSDP Sites 58-445 and 58-446 - Yoshiaki Sato (PANGAEA, 1980)
Heavy-mineral analyses were made for 39 samples, 27 from DSDP Site 445 and 12 from Site 446. About one-fourth of the samples were so loose that they were easily disaggregated in water. The amount of heavy residue and the magnetite content of the heavy fraction were very high, 0.2 to 44 per cent and (on the average) more than 20 per cent, respectively. Among the non-opaque heavy minerals, common hornblende (0 to 80%) and augite (0 to 98%) are most abundant. Pale-green and bluish-green amphiboles (around 10%) and the epidote group (a few to 48%) are next in abundance. Euhedral apatite and biotite and irregularly shaped chromite are not abundant, but are present throughout the sequence. Hacksaw structure is developed in pale-green amphibole and augite. At Site 445, a fair amount of chlorite and a few glauconite(?) grains are present from Core 445-81 downward. The content of common hornblende and opaque minerals also changes from Core 445-81 downward. A geological boundary may exist between Cores 445-77 and 445-81. Source rocks of the sediments at both sites were basaltic volcanic rocks (possibly alkali suite), schists, and ultramafic rocks. The degree of lithification and amount of heavy residue, and the content of magnetite, non-opaque heavy minerals (excluding mafic minerals), and mafic minerals in the cores were compared with Eocene, Oligocene, and Miocene sandstones of southwest Japan. In many respects, the sediments at Sites 445 and 446 are quite different from those of southwest Japan. From the early Eocene to the early Miocene, the area of these sites belonged to a different geologic province than southwest Japan.
Supplement to: Sato, Y (1980): Heavy-mineral composition of tertiary sediments at Deep Sea Drilling Project Sites 445 and 446, northeastern Philippine Sea. In: deVries Klein, G; Kobayashi, K; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 58, 661-667, https://doi.org/10.2973/dsdp.proc.58.117.1980